2000
DOI: 10.1097/00003246-200005000-00056
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of pediatric and neonatal endotracheal tubes: Influence of flow rate, size, and shape

Abstract: Our results suggest that the use of a small-diameter, straight ETT will significantly increase the work of breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 8 publications
4
67
1
3
Order By: Relevance
“…Previous studies showed that correction does not guarantee a better approximation of Rrs. 152,164 In contrast to our findings, Lischka and colleagues described significant associations between their score and Crs within 24 hours after birth. 154 Others described correlations between Giedion scores and parameters of lung function 43,124 , However, these studies were performed before exogenous surfactant therapy had been widely introduced.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that correction does not guarantee a better approximation of Rrs. 152,164 In contrast to our findings, Lischka and colleagues described significant associations between their score and Crs within 24 hours after birth. 154 Others described correlations between Giedion scores and parameters of lung function 43,124 , However, these studies were performed before exogenous surfactant therapy had been widely introduced.…”
Section: Discussioncontrasting
confidence: 99%
“…Since endotracheal tube size substantially affects Rrs measurements during mechanical ventilation, 152,164 Rrs,neo was subsequently corrected for this effect by including tube diameter in all regression models. In these cases, we will refer to Rrs,neoC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effects of artificial airways on spontaneous breathing during mechanical ventilation are well studied, their effects on work of breathing during bag mask ventilation or applied CPAP are not. 7 Resistance to flow is a critical factor when providing ventilation or CPAP to the spontaneously breathing infant. Imposed work of breathing can occur when a patient must breathe spontaneously through an artificial apparatus placed between the lungs and the air, such as ETTs, ETCO 2 detectors, flow sensors, and expiratory valves.…”
Section: Discussionmentioning
confidence: 99%